Obesity and Atrial Fibrillation: A Comprehensive Review - Jonathan Na; Sai Sita Garapati; Adi Lador (Methodist DeBakey Cardiovascular Journal)
Atrial fibrillation (AF) remains the most common arrhythmia worldwide, but its pathophysiology remains complex and multifactorial. As obesity has increased over the past couple of decades, much interest has been generated about its relationship with other diseases. As a result, the interplay between AF and obesity has been rigorously investigated as risk factor modification has become more important for the management of AF. In this review, we discuss the epidemiology of AF and obesity, the pathophysiology connecting these two diseases, and how obesity affects the management of AF.